Progressive Limb Weakness in A Young Man: A Case Report of POEMS Syndrome (Bangladesh Journal of Neuroscience, 2019)
Polyneuropathy is an initial presentation and essential feature of POEMS ( polyneuropathy, organomegaly, endocrinopathy, M-protein, and skin changes) syndrome. Neuropathy is typically distal, symmetric and slowly progressive with demyelinating changes. After a gradual proximal spread, it usually results in severe muscle weakness and functional disabilities. In the present report, we describe a 40-year-old diabetic male presented with gradually progressive weakness of both lower limbs for 1 year followed by the involvement of both upper limbs for the last 3 months. On examination hyperpigmentation, lymphadenopathy, gynecomastia, anasarca, hepatomegaly, bilateral optic disc swelling, sensory-motor polyneuropathy was found. Laboratory findings showed IgG lambda monoclonal gammopathy, raised VEGF, sensory-motor demyelinating and axonal polyneuropathy. All findings were consistent with POEMS syndrome. The patient was treated with lenalidomide and dexamethasone cyclical therapy with some clinical improvement.Bangladesh Journal of Neuroscience 2019; Vol. 35 (1): 51-56